2015
DOI: 10.1002/etc.2897
|View full text |Cite
|
Sign up to set email alerts
|

Critical predicted no effect concentrations (PNECs) should not be based on a single toxicity test

Abstract: Predicted no-effect concentrations (PNECs), which represent the concentration of a substance below which an unacceptable effect most likely will not occur, are widely used for risk assessment and in environmental policy and regulation. They are typically based on single-species laboratory toxicity tests; often, a single test result for the most sensitive endpoints drives the derivation of a PNEC. In the present study, the authors provide a case study emphasizing the importance of determining the reliability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Each batch of synthetic lake water was analyzed for its ionic composition to assess concentrations of the major ions and to calculate TDS concentrations. Results of those analyses confirmed that the calculated TDS concentrations for the synthetic lake water batches ranged from 1380 to 1520 mg/L, within 10% of the target nominal concentration of 1500 mg/L (Chapman and Elphick ), and from 2030 to 2200 mg/L, again within 10% of the target nominal concentration of 2000 mg/L.…”
Section: Methodsmentioning
confidence: 56%
See 3 more Smart Citations
“…Each batch of synthetic lake water was analyzed for its ionic composition to assess concentrations of the major ions and to calculate TDS concentrations. Results of those analyses confirmed that the calculated TDS concentrations for the synthetic lake water batches ranged from 1380 to 1520 mg/L, within 10% of the target nominal concentration of 1500 mg/L (Chapman and Elphick ), and from 2030 to 2200 mg/L, again within 10% of the target nominal concentration of 2000 mg/L.…”
Section: Methodsmentioning
confidence: 56%
“…All point estimates are presented as calculated TDS concentrations. Additional details are provided in Golder (); Chapman (, , ); Baker et al (); Marus et al (); and Chapman and Elphick (). Control performance met test acceptability criteria for all test methods, and test results were corrected for mean control responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other, Ceriodaphnia dubia, was not a representative of a resident genus or species. Five D. magna 21-d tests gave useful, acceptable data [10]. Six C. dubia 7-d tests that met all guidlines but guideline 7 resulted in no or negligible effects endpoints that ranged from similar to those derived for D. magna and other tested species (3 other invertebrates, 2 algae, 3 fish; all but 2 were sitespecific taxa) to lower than total dissolved solid concentrations that presently are not adversely affecting waterflea populations living in the receiving water body.…”
Section: The Geometric Mean In Ecotoxicologymentioning
confidence: 99%